Integrating Philosophy of Understanding With the Cognitive Sciences - Khalifa, Kareem; Islam, Farhan; Gamboa, J. P.; Wilkenfeld, Daniel A.; Kostić, Daniel (Frontiers in Systems Neuroscience, 2022)
We provide two programmatic frameworks for integrating philosophical research on understanding with complementary work in computer science, psychology, and neuroscience. First, philosophical theories of understanding have consequences about how agents should reason if they are to understand that can then be evaluated empirically by their concordance with findings in scientific studies of reasoning. Second, these studies use a multitude of explanations, and a philosophical theory of understanding is well suited to integrating these explanations in illuminating ways.